Sub-suppliers model 4.0 and knowledge discovery in industry supply chain - Milena KRUMOVA; Evgeniy PETROV (Smart Cities and Regional Development Journal)
Web 4.0 revolution and the abundance of industrial data in the current business environment allow each industrial company to innovate in a diversity of ways. The novelty approaches for the industry are often related to Industry 4.0, where data plays a key role. This research paper aims to develop a new model of the Sub-Supplier process description „Sub-Suppliers Model 4.0“. The model presents the role of knowledge management and Web 4.0 as having a key impact on the processes for business value creation for the industrial organisation. The paper is structured into three chapters. The introduction presents the methods used along with the research question. Chapter one starts with the theoretical bases and state of the art of the Industrial Sub-Supplier Process (ISSP). Chapter two makes a link between the ISSP, knowledge management and knowledge discovery process using data from Supply Chain Management Software for management decision-making. Chapter three of the research starts with web 4.0 tools and proposes a Sub-Suppliers Model 4.0, while trying to explain how the ISSP can be optimized based on the KPIs used. The main research contribution is the novelty integration of the knowledge discovery concept and the implementation of web 4.0 tools into the ISSP.